Frontispiece: Theory Uncovers the Role of the Methionine–Tyrosine–Tryptophan Radical Adduct in the Catalase Reaction of KatGs: O2 Release Mediated by Proton‐Coupled Electron Transfer. Issue 20 (10th April 2018) - Wang, Binju; Fita, Ignacio; Rovira, Carme
Abstract : Nature has evolved a unique covalent M‐Y‐W adduct in the active site of catalase−peroxidase (KatGs) to catalyze the decomposition of exessive hydrogen peroxide through the catalase reaction, but the exact role of the adduct in this reaction was elusive up to now. Here, QM/MM calculations and QM/MM metadynamics simulations are employed to elucidate the molecular mechanism of the catalase reaction in KatGs. This study demonstrates that the M‐Y‐W adduct acts as an electron sink to mediate O2 release via a novel proton‐coupled electron transfer mechanism. For more details see the Full Paper by C. Rovira et al. onpage 5388 ff.